2021
DOI: 10.3389/fphar.2021.729568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trandolapril on Structural, Contractile and Electrophysiological Remodeling in Experimental Volume Overload Heart Failure

Abstract: Chronic volume overload induces multiple cardiac remodeling processes that finally result in eccentric cardiac hypertrophy and heart failure. We have hypothesized that chronic angiotensin-converting enzyme (ACE) inhibition by trandolapril might affect various remodeling processes differentially, thus allowing their dissociation. Cardiac remodeling due to chronic volume overload and the effects of trandolapril were investigated in rats with an aortocaval fistula (ACF rats). The aortocaval shunt was created usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
2
8
0
Order By: Relevance
“…In accordance with ACF-induced increase of mitochondrial ROS production 28,29 . ACF-induced increases in right and left ventricle mass index, in HSD as well as TGR, as also shown previously in normotensive rats 10,15,27,30,31 . These parameters were utilized as markers of hypertrophy 32 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with ACF-induced increase of mitochondrial ROS production 28,29 . ACF-induced increases in right and left ventricle mass index, in HSD as well as TGR, as also shown previously in normotensive rats 10,15,27,30,31 . These parameters were utilized as markers of hypertrophy 32 .…”
Section: Discussionsupporting
confidence: 87%
“…Treatment with either drug supressed circulating ANP and TBARS levels in both heart ventricles and reduced heart mass index, including right and left ventricles regardless the rat strain. Likewise in HSD rats treated with trandolapril 30 . Moreover, treatment increased alkaline phosphatase activity in arterial part of capillary network in HSD as well as TGR that may contribute to improvement of heart function 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Jarkovska et al suggested the anti-arrhythmic effect of ACEi in ACF rats. 53 The present study has several limitations. Only the resting hemodynamics was tested, because of technical reasons we did not perform preload changing maneuvers (vena cava balloon inflation), and therefore we cannot report arterial and ventricular elastance values.…”
Section: Cgmp Tissue Levelsmentioning
confidence: 83%
“…Sarcometic contractions and calcium transients were measured as described previously [ 41 ]. The cardiomyocytes from the left ventricle ( n = 16–23 in each group) were incubated with 2-μmol/L-Fura-2-AM Tyrode solution for 20 min and then washed with Tyrode solution repeatedly.…”
Section: Methodsmentioning
confidence: 99%